In vitro Analysis of Tooth Movement Using Clear Aligners versus Traditional Brackets - Jeswin Abel; G. Ranjitha; N. Lingesh Kumar; Mahesh F. Balikai; Ayushi Singh; Arya Jayavarma (Journal of Pharmacy and Bioallied Sciences)
Introduction: Correcting malocclusions with controlled dental displacement is one of the objectives of orthodontic treatment. Materials and Methods: Over time, the two main treatment choices that have surfaced are the transparent aligners and the traditional braces. Results: This work explores the efficacy of clear aligners and conventional braces in terms of tooth movement, biomechanical features, and patient-centered outcomes using an in vitro approach. Conclusion: By means of movement correctness, velocity, and prospective consequences, the study offers a whole knowledge of the benefits and drawbacks connected with every therapy modality.